Systematic review and meta-analysis of the benefit of celecoxib in treating advanced non-small-cell lung cancer - Yi L; Zhang W; Zhang H; Shen J; Zou J; Luo P; Zhang J (Dove Medical Press, 2018)
Lilan Yi,* Wei Zhang,* Hongman Zhang, Jie Shen, Jingwen Zou, Peng Luo, Jian Zhang Department of Oncology, Zhujiang Hospital, Southern Medical University, Guangzhou, Guangdong, People’s Republic of China *These authors contributed equally to this work Background: The clinical benefit of a selective cyclooxygenase-2 inhibitor, celecoxib, combined with anticancer therapy in advanced non-small-cell lung cancer (NSCLC) remains unclear. A meta-analysis was performed to address the efficacy and safety of celecoxib in patients with advanced NSCLC. Materials and methods: Three databases, including PubMed, EMBASE, and the Cochrane Library, were systematically searched for available literature until March 1, 2018. Data on tumor response rates, one-year survival, overall survival, progression-free survival, and toxicities were extracted from the included randomized clinical trials. Subgroup analysis was carried out according to the line of treatment. Review Manager 5.3 software was applied to conduct the meta-analysis. Results: A total of 7 randomized controlled trials involving 1,559 patients with advanced NSCLC were enrolled for analysis. The pooled overall response rate (ORR) of celecoxib added to systemic therapy was not significantly improved (risk ratio [RR] =1.14, 95% CI =0.96–1.35, P=0.13). Additionally, no differences were observed between the celecoxib and placebo groups regarding 1-year survival (RR =0.99, 95% CI =0.88–1.12, P=0.91). Subgroup analysis showed that adding celecoxib to the first-line treatment significantly improved the ORR (RR =1.21, 95% CI =1.01–1.44, P=0.04) and partial response rate (RR =1.26, 95% CI =1.01–1.58, P=0.04). The aggregated Kaplan–Meier analysis found no significant difference between celecoxib and placebo regarding the 5-year overall survival (median, 12.9 vs 12.5 months, P=0.553) and 5-year progression-free survival (median, 7.4 vs 7.2 months, P=0.641). The increased RR of leukopenia (RR =1.25, 95% CI =1.03–1.50) and thrombocytopenia (RR =1.39, 95% CI =1.11–1.75) indicated that celecoxib increased hematologic toxicities (grade ≥III). However, celecoxib did not increase the related risks of thrombosis or embolism (RR =1.26, 95% CI =0.66–2.39) and cardiac ischemia (RR =1.16, 95% CI =0.39–3.44). Conclusion: Celecoxib had no benefit on survival indices for advanced NSCLC but improved the ORR of first-line treatment. Additionally, celecoxib increased the rate of hematologic toxicities without increasing the risk of cardiovascular events. Keywords: celecoxib, non-small-cell lung cancer, NSCLC, systematic review, meta-analysis